2010
DOI: 10.1097/ede.0b013e3181f20bed
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Use of Acetaminophen, Ibuprofen, and Acetylsalicylic Acid During Pregnancy and Risk of Cryptorchidism

Abstract: Maternal intake of acetaminophen for more than 4 weeks during pregnancy, especially during the first and second trimesters, may moderately increase the occurrence of cryptorchidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(137 citation statements)
references
References 35 publications
6
126
0
Order By: Relevance
“…Figure 4 Mild analgesic compounds paracetamol and acetylsalicylic acid reduced PGD2 and testosterone production in ex vivo cultured GD14.5 rat supported by an independent Danish study of 47 400 boys with an incidence of cryptorchidism (2%) similar to that observed in the Finnish cohort (Jensen et al, 2010). In that study, they report a significant association between the use of paracetamol in weeks 8-14 and cryptorchidism (Jensen et al, 2010). We did not find an association with hypospadia in any of the birth cohorts; however, the incidence of hypospadia was very low at birth (1% in the Danish and 0.3% in the Finnish cohort) and it is not clear how large the association is between cryptorchidism and hypospadia (Akre and Richiardi, 2009;Jørgensen et al, 2010).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 4 Mild analgesic compounds paracetamol and acetylsalicylic acid reduced PGD2 and testosterone production in ex vivo cultured GD14.5 rat supported by an independent Danish study of 47 400 boys with an incidence of cryptorchidism (2%) similar to that observed in the Finnish cohort (Jensen et al, 2010). In that study, they report a significant association between the use of paracetamol in weeks 8-14 and cryptorchidism (Jensen et al, 2010). We did not find an association with hypospadia in any of the birth cohorts; however, the incidence of hypospadia was very low at birth (1% in the Danish and 0.3% in the Finnish cohort) and it is not clear how large the association is between cryptorchidism and hypospadia (Akre and Richiardi, 2009;Jørgensen et al, 2010).…”
Section: Discussionsupporting
confidence: 58%
“…Data represent the mean + SEM. Figure 4 Mild analgesic compounds paracetamol and acetylsalicylic acid reduced PGD2 and testosterone production in ex vivo cultured GD14.5 rat supported by an independent Danish study of 47 400 boys with an incidence of cryptorchidism (2%) similar to that observed in the Finnish cohort (Jensen et al, 2010). In that study, they report a significant association between the use of paracetamol in weeks 8-14 and cryptorchidism (Jensen et al, 2010).…”
Section: Discussionmentioning
confidence: 56%
“…The anti-androgenic effect of paracetamol in developmentally exposed rats is corroborated by findings of reduced testosterone production in ex vivo fetal rat testes (Kristensen et al 2011(Kristensen et al , 2012 and by in vitro findings in adult human testes (Albert et al 2013). Furthermore, PM exposure during fetal development in humans has also been associated with increased risk of cryptorchidism in several epidemiological studies (Jensen et al 2010, 2011a, Kristensen et al 2011, Snijder et al 2012, indicating that the effects seen in the rats could be indicative of adverse effects in humans. Further examination of endocrine-sensitive endpoints later in life may clarify whether this anti-androgenic effect of paracetamol causes permanent adverse reproductive effects.…”
Section: Discussionmentioning
confidence: 73%
“…The study reported that APAP and prenatal exposure had a higher numbers of baby boys with congenital cryptorchidism. Undescended testes may be linked with alarming risk of testicular germ cell tumors, reduced fertility and psychological adverse events when the baby is grown [17]. Prostaglandins are assumed to be implicated in the differentiation of the testis and the male genital tract [18,19].…”
Section: Cryptorchidism and Acetaminophenmentioning
confidence: 99%